Effects of novel 17β-hydroxysteroid dehydrogenase type 10 inhibitors on mitochondrial respiration. (15th March 2021) - Fišar, Zdeněk; Musílek, Kamil; Benek, Ondřej; Hroch, Lukáš; Vinklářová, Lucie; Schmidt, Monika; Hroudová, Jana; Raboch, Jiří
Graphical abstract: Highlights: Mitochondrial in vitro effect of 42 novel modulators of 17β-HSD was tested. Inhibition of complex I-linked respiration occurs at high drug concentration. Inhibition of complex II-linked respiration was negligible for most molecules. Most of tested drugs were selective monoamine oxidase type A inhibitors. Six of the 42 new compounds had minimal effect on mitochondrial function. Abstract: Mitochondrial enzymes are targets of newly synthesized drugs being tested for the treatment of neurodegenerative disorders, such as Alzheimer's disease (AD). The enzyme 17β-hydroxysteroid dehydrogenase type 10 (HSD10) is a multifunctional mitochondrial protein that is thought to play a role in the pathophysiology of AD and is one of the targets of new potential AD drugs. The in vitro effects of frentizole, riluzole, AG18051, and 42 novel modulators of HSD10 (potential AD drugs) on citrate synthase (CS) activity, monoamine oxidase (MAO) activity, complex I- or complex II-linked mitochondrial respiratory rate, and complex I activity were measured in isolated pig brain mitochondria. Based on their minimal inhibitory effects on the respiratory rate of mitochondria and CS and complex I activity, six novel compounds were selected for further testing. Assuming that inhibition of MAO-B could be a desirable effect of AD drugs, only AG18051 and one new compound met the criteria for MAO-B inhibition with minimal drug-induced effects on mitochondrial respiration. In conclusion, our in vitro screening of mitochondrial effect of novel potential AD drugs has enabled the selection of the most promising molecules for further testing that are relatively safe in terms of drug-induced mitochondrial toxicity.